Effect of authentic chemistry problem solving competency in solving open-ended problems - Muhamad, Suraiya (2018)
Problem-solving competency assists students when they apply their scientific knowledge, experiences and skills in the learning process. This study was conducted in order to develop module for authentic chemistry problem-solving competency (MAC-PSC). The module can be used to enhance the development of problem* solving competency when solving open-ended problems in chemistry. Prior to the development of this module, a preliminary study (n=112) was conducted to determine the levels of Chemistry problem-solving ability and skills among students. In addition, this study also investigated process and underlying factors involved in solving open-ended problems when learning Chemistry. Results showed that the students who were involved in the study had a moderate level of chemistry problemsolving ability and skills. Findings from the preliminary study were used to design and develop the Module for Authentic Chemistry Problem Solving Competency (MAC-PSC). A quasi experiment with a control group (n=47) and an authentic group (n=46) was adopted in the implementation phase. After using the Module (MACPSC) for six weeks, performance of students in pre and post chemistry problemsolving ability test (CPSAT) showed a significant positive effect. In addition students' development of Chemistry problem-solving competency to solve openended problems was also being investigated. This study identified these factors; (1) application of appropriate problem-solving skills, (2) deep conceptual understanding of scientific knowledge, (3) engaged in real life tasks, (4) collaborative problemsolving, (5) refer to experts, (6) accessible to multiple resources, (7) familiar with solving open-ended problems and (8) reflective writing practice, to be the key elements that catalysed the development of problem-solving competency when learning Chemistry. These key elements are useful for educators when designing learning strategies aimed at enhancing problem-solving competency among school students.